DETERMINANTS OF THE EFFECTIVENESS OF REGIONAL FINANCIAL MANAGEMENT WITH INFORMATION TECHNOLOGY AS A MODERATING VARIABLE - WINAR SEKAR ARUM; Dwi Orbaningsih; Djuni Farhan (Jurnal Magister Akuntansi Trisakti, 2026)
This study aims to examine the effect of communication (X₁), resources (X₂), disposition (X₃), and bureaucratic structure (X₄) on the effectiveness of regional financial management (Y), as well as to test the moderating role of information technology (Z). This study employs a quantitative approach using a survey method. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 25. The results indicate that disposition and bureaucratic structure have a positive and significant effect on the effectiveness of regional financial management, while communication and resources do not show a significant effect. Furthermore, information technology is found to moderate only the relationship between bureaucratic structure and financial management effectiveness, indicating its role in strengthening structural governance mechanisms. However, information technology does not moderate the effects of communication, resources, or disposition. These findings highlight that the effectiveness of regional financial management is primarily determined by the behavioral and structural aspects of the organization. Theoretically, this study contributes to the development of public sector governance by emphasizing the interaction between organizational structure and technological support. Practically, the results suggest that optimizing bureaucratic structures supported by information technology can enhance financial management effectiveness.